Definition of a Component Selection Process Based on QoS Criteria and Its Application to Self-adaptive Software Systems - Silva, Daniel Cunha da; Lopes, Adilson Barboza; Leite, Jair C.; Pinto, Felipe A. P.; Silva, Carlos Eduardo da (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
Nowadays, self-adaptive systems use the concept of feedback loops. This approach is based on the selection of components that conform to the expected requirements. The selection became increasingly complex in such systems due to the variety of criteria. This paper proposes a process for dynamic selection of components using multi-attribute utility theory based on Quality of Service (QoS) criteria. Furthermore, it defines a model that can be used to represent the current needs of an application, and that is used by the proposed selection process for evaluating the candidate components. As a proof of concept, it's presented the AnaMoC module that performs the selection of components based on the proposed process.